Hubungan Antara Pola Asuh Orang Tua Dengan Tingkat Keberhasilan Toilet Training Pada Anak Usia Prasekolah di Kelurahan Mangsang - Diana Br Samosir; Umi Eliawati; Sri Muharni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Toilet training is a major problem during the growth and development of children aged 3 to 6 years in preschool. This can be influenced by the form of parental parenting with various series of procedures carried out to look after, care for and educate children consistently which can be realized in the form of interactions between parents and their children. There is a phenomenon that often occurs, namely that there are still many preschool children who fail in implementing toilet training because the success of toilet training cannot be separated from the role of appropriate and good parenting, so children will be more independent and successful in toilet training more quickly. Objective: to be able to see the relationship between parenting patterns and the success rate of toilet training in preschool-aged children in Mangsang Village. Method: This research is a quantitative descriptive study with a cross sectional approach with sampling carried out using total sampling. The instrument used in this research was a questionnaire with 48 parents as respondents. Results: It is known using the chi-square statistical test where the p value is 0.000 <0.05, which means Ha is accepted and Ho is rejected. Conclusion: there is a significant relationship between parenting styles and the success rate of toilet training in preschool-aged children in Mangsang Village.